FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI DESA SUMENGKO KECAMATAN SUKOMORO KABUPATEN NGANJUK - Ricky Bagus Manggala; Arfida Boedirochminarni (Jurnal Ilmu Ekonomi JIE, 2018)
This study has the objectives of (1) Describe the profile of wetland field, farmers' capital, labor and production in rice farming in Sumengko Village. (2) To analyze the influence of wetland field, farmer's capital, and labor to rice production in Sumengko Village. In the research using quantitative type, sampling technique using Proporsional Area Random Sampling obtained 92 samples. The research variables correlate between dependent and independent variable, dependent variable consists of Wetland Field, Capital and Labor. While the independent variable is Rice Production. The method used is descriptive analysis and multiple linear regression analysis. The result of descriptive research shows that the widest area of paddy fields owned by farmers is0,084 - 0,697 ha, the most used capital is around Rp. 1.210.000 - 7.931.000, the most manpower used is about 29 - 48 people, and the highest Production of Rice produced is 5 - 47 kw. While the results of research using regression analysis and variable variables hypothesis of wetland, capital and labor positive and significant to rice production in Sumengko Village, Sukomoro Sub-District, Nganjuk RegencyKeywords: Production, Wetland Field, Capital, and Labor